2008
DOI: 10.1371/journal.pone.0004059
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the Xylella fastidiosa Prophage-Like Regions and Their Impact in Genome Differentiation

Abstract: Xylella fastidiosa is a Gram negative plant pathogen causing many economically important diseases, and analyses of completely sequenced X. fastidiosa genome strains allowed the identification of many prophage-like elements and possibly phage remnants, accounting for up to 15% of the genome composition. To better evaluate the recent evolution of the X. fastidiosa chromosome backbone among distinct pathovars, the number and location of prophage-like regions on two finished genomes (9a5c and Temecula1), and in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
48
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 54 publications
5
48
0
3
Order By: Relevance
“…X. fastidiosa genomes contain high levels of phage and phage-like regions (de Mello Varani et al 2008;Nunes et al 2003;Van Sluys et al 2003), and natural competence could be a mechanism to help cells eliminate new integration of these regions by recombining the homologous DNA without phage sequences, as suggested by a recent study (Croucher et al 2016). Other studies have reported restriction-modification (R-M) systems limiting transformation frequency (Niza et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…X. fastidiosa genomes contain high levels of phage and phage-like regions (de Mello Varani et al 2008;Nunes et al 2003;Van Sluys et al 2003), and natural competence could be a mechanism to help cells eliminate new integration of these regions by recombining the homologous DNA without phage sequences, as suggested by a recent study (Croucher et al 2016). Other studies have reported restriction-modification (R-M) systems limiting transformation frequency (Niza et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One conclusion from these analyses is that phage may have played a significant role in the evolution of X. fastidiosa (19,44,53). Phage-related sequences make up between 9% and 15% of the Xylella genomes, and 47 phage elements were identified in four genomes (18). Many strain-specific differences are located in prophage (18).…”
mentioning
confidence: 99%
“…Phage-related sequences make up between 9% and 15% of the Xylella genomes, and 47 phage elements were identified in four genomes (18). Many strain-specific differences are located in prophage (18). Most of the prophage elements appeared to be the result of independent insertion events, implying that active phages are frequently encountered.…”
mentioning
confidence: 99%
See 2 more Smart Citations